Collaboration in the Healthy Living Community Movement in Kaloloa Village, Samaturu District, Kolaka Regency - Ashari Ashari; Sudirman Baso (KASTA : Jurnal Ilmu Sosial, Agama, Budaya dan Terapan, 2026)
The Healthy Living Community Movement (GERMAS) cannot only rely on the role of the health sector but needs support and in its implementation is supported by other Regional Apparatus Organizations (OPD) and collaborates with the government at the sub-district and village levels to improve public health. This study aims to determine and describe how the collaboration carried out by the Village Government and the Health Office in the Healthy Living Community Movement in Kaloloa Village, Samaturu District, Kolaka Regency. This study is a qualitative descriptive study, informants in this study were fifteen people. Data collection techniques were direct observation, direct interviews. The data analysis used was Data Reduction, Data Presentation, Drawing Conclusions. The results of this study indicate that the collaboration between the Village Government and the Kolaka Regency Health Office in the context of Germas activities in Kaloloa Village, Samaturu District, Kolaka Regency has not been implemented well because the collaboration process that was built did not involve the community as the object of Germas activities. This is because the community was not included in making compromises so that there are people who are not aware of the Germas program and the lack of public knowledge due to the lack of information either through socialization or dissemination of information through banners and billboards related to the Germas program.